Adoption of Tissue Culture in Horticulture: A Study of Banana-Growing Farmers in Andhra Pradesh - Ch. Krishna Rao,; E. Haribabu, (Journal of Agricultural Extension Management, 2025)
Horticulture is one of the al lied areas of agriculture where technology improvement has been contributing to increased productivity over time. Horticulture deals with breeding, cultivation, pest management and postharvest technology of plants that produce ornamental flowers, fruits, vegetables and spices. India is second in fruit and vegetable production in the world. However, India's share in global export of horticultural commodities is negligible due to low productivity, lack of infrastructural facilities and inadequate post-harvest management